The mediating role of perceived value in the relationship between halal destination attributes and muslim tourist loyalty: Halal Tourism - Afriansyah, Femra; Wardi, Yunia (Universitas Negeri Padang, 2024)
This study aims to prove and analyze the influence of halal tourism on the loyalty of Muslim tourists traveling to Padang City with perceived value. This study used 60 respondents who were Muslim tourists visiting halal tourist attractions in Padang City, sampling was carried out using purposive sampling techniques. Data and information collection was carried out using the census method, namely by distributing questionnaires directly. The data analysis method used was path analysis and t-statistic testing. In accordance with the results of the hypothesis testing, it was found that halal tourism had a significant effect on tourist loyalty, in the hypothesis testing procedure it was also found that perceived value had a positive effect on tourist loyalty to visit halal tourist attractions in Padang City, then in the indirect influence test it was found that perceived value was able to mediate the relationship between halal tourism and the loyalty of Muslim tourists traveling to halal tourist attractions in Padang City.